2015
DOI: 10.1016/j.ijsu.2015.05.028
|View full text |Cite
|
Sign up to set email alerts
|

Urinary reconstruction after kidney transplantation: Pyeloureterostomy versus ureteroneocystostomy

Abstract: A best evidence topic in transplant surgery was written according to a structured protocol. The question addressed was: In adults undergoing renal transplantation, does pyeloureterostomy, as compared to ureteroneocystostomy, improve clinical outcomes? A total of 235 articles were identified using the search protocol described, of which six represented the best evidence available to answer the clinical question. The authors, journal, date and country of publication, patient group studied, study type, relevant o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 7 publications
0
3
0
2
Order By: Relevance
“…The transplant kidney ureter can be anastomosed to the recipient urinary bladder, often at the dome (ureteroneocystostomy), or alternatively to the recipient's native ureter after removal of the diseased native kidney using an end-toside anastomosis (ureteroureterostomy), in cases where the length of the transplant ureter is insufficient or the recipient bladder anatomy precludes ureteroneocystostomy (29). Pyeloureterostomy is an additional technique that involves recipient nephrectomy with preservation of the recipient ureter, which is anastomosed to the donor renal pelvis (22,30).…”
Section: Teaching Pointsmentioning
confidence: 99%
“…The transplant kidney ureter can be anastomosed to the recipient urinary bladder, often at the dome (ureteroneocystostomy), or alternatively to the recipient's native ureter after removal of the diseased native kidney using an end-toside anastomosis (ureteroureterostomy), in cases where the length of the transplant ureter is insufficient or the recipient bladder anatomy precludes ureteroneocystostomy (29). Pyeloureterostomy is an additional technique that involves recipient nephrectomy with preservation of the recipient ureter, which is anastomosed to the donor renal pelvis (22,30).…”
Section: Teaching Pointsmentioning
confidence: 99%
“…Pyeloureterostomy is a well-known option for urinary tract reconstruction during kidney transplantation (3,4,8,24,26) as well as for the treatment of ureteroneocystostomy complications (10)(11)(12)(13). At least two surgical techniques, end-to-end and end-toside anastomosis, have been performed.…”
Section: Discussionmentioning
confidence: 99%
“…Classical techniques for urinary tract reconstruction during a kidney transplant surgery include reimplantation of the kidney donor ureter with the recipient´s bladder (ureteroneocystostomy) or with the recipient's native ureter (pyeloureterostomy or ureteroureterostomy). While both techniques show similar urological complication rates, most transplant centers initially opt for a ureteroneocystostomy using the Lich-Gregoir technique (1)(2)(3), deferring the use of ureteroureterostomy, usually without ipsilateral nephrectomy, as a secondary option in case of complications in the ureteroneocystostomy anastomosis, such as urinary leak and ureteral stenosis (3)(4)(5)(6)(7)(8)(9)(10). Although some reports have shown that the native ureter ligation without nephrectomy is safe (3)(4)(5)(6)(7)(8), this technique may cause hydronephrosis, primarily in patients with significant residual diuresis, and eventually discomfort or lumbar pain.…”
Section: Introductionmentioning
confidence: 99%
“…A pyeloureterostomia irodalma szintén kiterjedt. Norris és mtsai 235 közleményt áttekintve arra a követ-keztetésre jutottak, hogy ez a módszer kevéssé használt, és nincsenek prospektív vizsgálatok a témában, ugyanakkor ajánlják a cadavervese-átültetéseknél, ahol a donorureter vérellátása kérdéses lehet [23]. Kevés szó esik az alternatív technikának tekintett ureteroureterostomiák-ról, elsősorban a beszűkült neocystostomia utáni reoperációk vagy atrophiás húgyhólyag esetén ajánlják [24].…”
Section: áBraunclassified
“…Ezt a saját anyagunk az eddigiek alapján alá-támasztani látszik. Az ureterrekonstrukciók sebészi lehetőségeinek bővítése mindenképpen előnyt jelent [23].…”
Section: áBraunclassified